Investigations of milk-fat lamp production practices for Western Kansas - Menzies, C.S.; Hillman, M.; Banbury, Evans E. (Kansas Agricultural Experiment Station, 2011)
The Colby ewe flock consists of approximately 325 four-and five-year-old fine-wool ewes, that were purchase in southwest Texas as yearlings. Purebred Hampshire ewes are used. The first attempts to determine the effect that varying the energy intake of ewes during a preflushing period has on lambing performance of the ewes. The second test compares various rations for flushing ewes, and the third studies various management practices and rations for ewes and lambs.
Investigations of milk-fat lamp production practices for Western Kansas
Keywords: Sheep; Milk-fat lamb; Energy intake; Performance